Changes in the microbial community structure during the digitally managed fermentation of medium-temperature Daqu - CAO,Jinghua (2022)
Abstract Illumina MiSeq high-throughput sequencing technology was used to study the microbial community structure of medium-temperature Daqu produced via a digitally managed method and the traditional method. The relationship between the changes in physicochemical properties and microorganisms in Daqu during the fermentation process was analyzed. At the end of fermentation, the bacterial diversity of traditional medium-temperature Daqu was higher than that of digital medium-temperature Daqu, and there was no significant difference in the diversity of fungal communities. The dominant bacteria were Weissella, Lactobacillus, Pediococcus and Saccharopolyspora. The dominant fungi were Thermoascus, Issatchenkia and Candia. On the 25th day of fermentation, the bacterial community distribution in the digital Daqu was more even than that in the traditional Daqu, but the fungal community distribution was the opposite. The results of nonmetric multidimensional scale (NMDS) analysis and canonical correlation analysis (CCA) show that Daqu produced by the two fermentation methods had many similarities.